Creation of personal visual identity for grafic letterer - Ulyanova, Elizaveta; Khabirova, Maja; Phung, Hyu Nghia; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
In this bachelors thesis, I decided to focus on the topic of personal branding. The aim of this work is to propose a visual identity for me as for a lettering artist.(letterer) The magnitude of personal branding for freelance designers is thoroughly discussed in the introductory part. Corporate and personal branding and the differences between them are defined in the theoretical part. Knowledge gained early is subsequently applied to use in the next part. The practical part is split into different sections. Those sections describe creation process for logo design, personal website and its simpler version for mobile users, business cards and resume. I presented a way for designing your own personal branding that will prove beneficial for freelancers. The most important result of my thesis is a creation of personal branding that is essential for achieving better results in my field.
Vedoucí práce: Maja Khabirova
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses